1997
DOI: 10.1038/sj.onc.1201395
|View full text |Cite
|
Sign up to set email alerts
|

A functional analysis of p53 during early development of xenopus laevis

Abstract: p53 is a nuclear protein that acts like a tumor suppressor and is involved in regulation of cellular growth. In Xenopus, the p53 protein is highly expressed during oogenesis and is strictly cytoplasmic in the oocyte. We have analysed its participation in DNA replication and transcription during early development, using the egg and oocyte as model-systems. The injection of sperm nuclei into Xenopus eggs is followed by DNA replication and mitotic events. We show that the endogenous p53 enters the nuclei and move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
0
14
1
1
Order By: Relevance
“…In oocytes, all p53 appears to be cytoplasmic and therefore unlikely to be involved in transcription (30). During the postfertilization cleavage divisions, a small fraction of p53 translocates into the nucleus at each division (31), but since transcription is largely absent from embryos until the midblastula transition (12th cleavage), it is unlikely that p53 is involved in transcription-dependent processes. Instead, in early embryos, it has been suggested to play a role in S phase regulation and in DNA repair, to prevent reinitiation of DNA replication during S phase, and to block premature entry from S phase into mitosis (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oocytes, all p53 appears to be cytoplasmic and therefore unlikely to be involved in transcription (30). During the postfertilization cleavage divisions, a small fraction of p53 translocates into the nucleus at each division (31), but since transcription is largely absent from embryos until the midblastula transition (12th cleavage), it is unlikely that p53 is involved in transcription-dependent processes. Instead, in early embryos, it has been suggested to play a role in S phase regulation and in DNA repair, to prevent reinitiation of DNA replication during S phase, and to block premature entry from S phase into mitosis (50).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group showed that Xenopus p53 is able to inhibit Aurora A kinase activity in vitro, but this inhibitory effect can be suppressed by prior binding of Aurora A to TPX2 (9). Contrary to somatic cells, where p53 is nuclear, unstable, and expressed at a very low level, p53 is highly expressed in the cytoplasm of Xenopus oocytes and stable until later stages of development (30,31). The high concentration of both p53 and Aurora A in the oocyte provided a suitable basis for investigating p53-Aurora A interaction and also evaluating Xenopus p53 as a substrate of Aurora A.…”
mentioning
confidence: 99%
“…p53 has a key role in sensing DNA damage and cell cycle regulation (for review see Levine, 1997) whilst also being involved in the regulation of di erentiation (Amariglio et al, 1997;Sabapathy et al, 1997;Shounan et al, 1996;Soddu et al, 1996). Alterations in p53 expression are heavily implicated in CML disease progression (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of this cell line with various DNA damaging agents led to phenotypes indistinguishable from those observed in mammalian cells, including both cell cycle arrest and apoptosis. It has been previously shown that Xp53 is stored in the cytoplasm of oocytes and migrates to the nucleus after fertilization (Amariglio et al, 1997;Tchang and Mechali, 1999). Such delocalization could act by supplying the p53 necessary for the protection of the embryo during the development.…”
Section: Phosphorylation Of Xp53 Led To Its Activation For Dna Bindingmentioning
confidence: 99%